PERSEPSI MASYARAKAT TENTANG PENGGUNAAN FORMALIN DALAM BAHAN MAKANAN DAN PELAKSANAAN PENDIDIKAN GIZI DAN KEAMANAN PANGAN - Wikanta, Wiwik (Bioedukasi Jurnal Pendidikan Biologi, 2010)
Formalin is not a preservative for foodstuffs and processed products.  But until recently, the use of formaldehyde in foodstuffs is still common. Whereas, nutrition and food security education for the community is still lacking.This study aimed to: (a) obtaining community about the use of formaldehyde in foodstuffs views of knowledge, attitude and behavior, and (2) obtaining community about the implementation of nutrition and food security education. Research using a sample survey method Sidoarjo urban communities with accidental sampling technique. Data collected by questionnaire and analyzed descriptively. The results showed that (1) almost all respondents knew there was food berformalin (90.91%); (2) examine the impact hazard (87.88%); (3) most feel uneasy (75.76%) and fear dangers affected (96.97%); (4) almost all respondents agreed formalin banned as a food preservative (90.91%), (5) most respondents (72.73%) has not made efforts to eliminate the formaldehyde in foodstuffs , and (6) almost all respondents (85.86%) Mersa not get enough nutrition education and food security. Conclusion: The public assumes that (1) the use of formalin in the food injurious to health and safety of consumers, (2) people need nutrition and food safety education are adequate. Kata Kunci:     persepsi,  formalin, bahan makanan, pendidikan,  gizi dan keamanan pangan